Gaya Bahasa dan Pesan Moral pada Lirik Lagu Bahasa Mandar (Suatu Kajian Stilistika) - Nur Hafsah Yunus, Muhammad Syaeba (Celebes Education Review, 2019)
Abstract. To understand language style and moral messages, the first thing to do is describe the language contained in the song's lyrics and then examine its aesthetic functions and valuesby stylistics theory. The purpose of this research is to describe the style of language and moral messages contained in the lyrics of the song Mandar. This type of research used in this research is descriptive qualitative. The method used in this research is a case study. The first stage, a preliminary study. The second stage, set / formulate the problem and determine the focus of research. The third stage, the study of literature and research analysis. The fourth step is collecting data. The fifth stage, data processing and interpretation. The sixth stage, making a research report. While for data collection, it is carried out by means of tests, observations, and documentation. The results showed that the linguistic style contained in the mandar song lyrics in broad outline, namely the opposing language style (hyperbole, litotes, antithesis), comparative language style (personification, hyperbole, metaphor, sinekdoke pars pro toto), affirmative language style (tautology, climax, repertis, anticlimax, inversion), while the moral message contained in the lyrics of the mandar song about the importance of maintaining loyalty and sharing in a relationship.